English historical linguistics historical English in contact : papers from the xxth ICEHL - Los, Bettelou (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2022)
"This volume drawn from the 20th International Conference on English Historical Linguistics (ICEHL, Edinburgh 2018) focuses on the role of language contact in the history of English. It showcases a wide variety of historical linguistic approaches, including 'big data' analyses of large corpora, dialectological methods, and the study of translated texts. It also breaks new ground by applying relevant insights from other fields, among them postcolonial linguistics and anthropology. This pluralistic approach brings new and under-studied issues within the scope of explanation, and challenges some long-held assumptions about the nature of historical change in English. The volume will be of interest to an audience interested in the history of English, and the impact of its contact with Viking Age Norse, Old French, and Latin"--